Pengembangan Sistem Keamanan Data Menggunakan Enkripsi AES-128 Berbasis Web: Studi Kasus pada Aplikasi NetCrypt (Kohesi: Jurnal Sains dan Teknologi, 2025)
The rapid advancement of information technology has increased the demand for robust data security systems to prevent unauthorized access to sensitive information. This study aims to design and develop a web-based system capable of performing data encryption and decryption using the Advanced Encryption Standard (AES) algorithm with a 128-bit key length. The application, named NetCrypt, is designed to secure important data by converting original information into an encrypted format, making it unreadable to unauthorized parties. The development process employs the Rapid Application Development (RAD) methodology, which allows for fast and flexible system development through iterative prototyping. Based on the testing results, the system successfully performs encryption and decryption operations and effectively maintains the confidentiality of data from external access. Therefore, NetCrypt has the potential to be an effective data security solution for web applications that require a high level of privacy protection.